Deconstruction of The Meaning of Beauty in Advertising Semiotic Analysis of Rexona Motion Activated Advertisement "72 Jam Kesegaran Nonstop” - Kuswara, Delvin Apriandi; Yusanto, Freddy (Lingkar Studi Komunikasi (LISKI), 2024)
This study aims to explain the deconstruction of the meaning of beauty depicted in the Rexona Motion Activated “72 Jam Kesegaran Nonstop” advertisement that aired in 2022 for a duration of 30 seconds. The reason behind this research is the evolution of advertisements shifting towards becoming agents of positive empowerment for women, particularly in representing beauty. The research uses a qualitative research method, and the data collected are analyzed through John Fiske's semiotic approach to television codes, consisting of Reality, Representation, and Ideology, as well as Jacques Derrida's deconstruction theory used as a reference in the research. The results of the study show a deconstruction of the meaning of beauty in the ad, moving away from the pseudo- "beautiful" construction by the media and the advertisement's effort to present beauty from within (inner beauty), which has been neglected by the media. Keywords: advertisement, deconstruction, semiotics, women, beauty